Early initiation of antiretroviral therapy for people newly diagnosed with HIV infection in Australia: trends and predictors, 2004–2015. Issue 6 (18th February 2019) - McManus, Hamish; Callander, Denton; Donovan, Basil; Russell, Darren B; O'Connor, Catherine C; Davies, Stephen C; Lewis, David A; Hellard, Margaret E; Chen, Marcus Y; Petoumenos, Kathy; Varma, Rick; Cogle, Aaron; et al.
Abstract: Objectives: To determine trends in and predictors of early treatment for people newly diagnosed with human immunodeficiency virus (HIV) infection in Australia. Design, setting: Retrospective cohort analysis of routinely collected longitudinal data from 44 sexual health clinics participating in the Australian Collaboration for Coordinated Enhanced Sentinel Surveillance (ACCESS) program. Participants: Patients diagnosed with HIV infections, January 2004 – June 2015. Main outcome measures: Commencement of antiretroviral therapy within 6 months of HIV diagnosis (early treatment); demographic, clinical, and risk group characteristics of patients associated with early treatment; trends in early treatment, by CD4 + cell count at diagnosis. Results: 917 people were diagnosed with HIV infections, their median age was 34 years (interquartile range [IQR]: 27–43 years), and 841 (92%) were men; the median CD4 + cell count at diagnosis was 510 cells/μL (IQR, 350–674 cells/μL). The proportion of patients who received early treatment increased from 17% (15 patients) in 2004–06 to 20% (34 patients) in 2007–09, 34% (95 patients) in 2010–12, and 53% (197 patients) in 2013–15 (trend, P < 0.001). The probability of early treatment, which increased with time, was higher for patients with lower CD4 + cell counts and higher viral loads at diagnosis. Conclusions: The proportion of people newly diagnosed with HIV in sexual health clinics in Australia who received treatment within 6 months of diagnosis increased from 17% to 53% during 2004–2015, reflecting changes in the CD4 + cell count threshold in treatment guidelines. Nevertheless, further strategies are needed to maximise the benefits of treatment to prevent viral transmission and morbidity.